Pengaruh Bahan Makanan, Kesadaran, Sertifikat Halal Terhadap Minat Beli Produk Halal Food Melalui Satisfaction Pada Masyarakat Kota Samarinda - Irwan, Sayid; Zilfana, Zilfana (Politeknik Raflesia Press, 2024)
This study focuses on food ingredients, halal awareness, and halal certification variables related to the interest in buying halal food products from consumers in Samarinda. The aim is to determine the effect of food ingredients, Halal Awareness, and Halal Certificates on the interest in buying Halal Food Products and add the Satisfaction variable in moderating the three variables. This research method uses a quantitative approach; the data sources used are primary and secondary data, and the population used in this study is the people of Samarinda. The sampling technique for this study uses purposive sampling technique, which is a sample selection technique where an individual selects a sample based on personal assessments of several criteria such as Religious (Muslim and Muslimah) appropriate characteristics of sample members, Foodstuffs on Satisfaction are known to have a positive insignificant effect, Halal Awareness of Satisfaction has a significant positive effect, Halal Certificate on Satisfaction has a significant positive effect,Satisfaction and Interest in Buying Halal Products have a significant positive effect, Foodstuffs through Satisfaction on Interest in Buying Halal Products have a positive insignificant effect, Halal Awareness through Satisfaction and Interest in Buying Halal Products has a significant positive effect, Halal Certificate through Satisfaction on Interest in Buying Halal Products has a value of having a significant positive effect.